Comparison of an integrated short-cut biological nitrogen removal process with magnetic coagulation treating swine wastewater and food waste digestate. (June 2021) - Ritigala, Tharindu; Chen, Yanlin; Zheng, Jiaxi; Demissie, Hailu; Zheng, Libing; Yu, Dawei; Sui, Qianwen; Chen, Meixue; Zhu, Jinxing; Fan, Hua; Li, Jiao; Gao, Qian; et al.
Graphical abstract: Highlights: Integrated MC and SMBR showed a new pathway for high strength wastewater treatment. MC showed high removals of TSS, turbidity, TP, and phosphate for both wastewaters. SMBR achieved stable and excellent removals of COD, TN, N H 4 + - N for both wastewaters. NAR achieved 74.54% and 76.02% for swine wastewater and FW digestate, respectively. Nitrosomonas and Diaphorobactor & Thaurea dominant in nitritation and denitritation. Abstract: An integration of two processes, magnetic coagulation (MC) and short-cut biological nitrogen removal (SBNR), coupled with a sequencing batch membrane bioreactor (SMBR) controlled by an automatic real-time control strategy (RTC), was developed to treat different characteristics of high strength wastewater. The treatment efficiency and microbial community-diversity of the proposed method was evaluated and investigated using swine wastewater and food waste (FW) digestate. The MC showed high removal of TSS (89.1 ± 1.5%, 92.21 ± 1.8%), turbidity (90.58 ± 2.1%, 95.1 ± 2.1%), TP (88.5 ± 1.9%, 92.1 ± 1.5%), phosphate (87.76 ± 1.6%, 91.22 ± 1.5%), and SMBR achieved stable and excellent removal of COD (96.05 ± 0.2%, 97.39 ± 0.2%), TN (97.30 ± 0.3%, 97.44 ± 0.3%) and N H 4 + - N (99.07 ± 0.2%, 98.54 ± 0.2%) for swine wastewater and FW digestate, respectively. The effluent COD and N H 4 + - N concentrations were found to meet their discharge standards. The microbial community comparison showed similar diversity and richness, and genus Diaphorobacter and Thaurea were dominant in denitritation, and Nitrosomonas was dominant in nitritation treating both swine wastewater and FW digestate.